New records of the rare pandalid shrimp Plesionika exigua (Rathbun, 1906 (Crustacea: Decapoda: Caridea) in the western Pacific - Chan, Tin-Yam (Zootaxa, 2016)
The rare species Plesionka exigua (Rathbun, 1906) is recorded for the first time from three western Pacific localities New Caledonia, Vanuatu and Ryukyu Islands of Japan. Redescription, illustrations on distinguishing characters and color photograph are provided for this poorly known species.